2013
DOI: 10.1007/s00784-013-0936-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MAGE-A tumor antigens and the efficacy of various chemotherapeutic agents in head and neck carcinoma cells

Abstract: These findings could affect the antineoplastic treatment of patients with MAGE-A11-positive tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…As described by their group, N0 cervical lymph node status was found more frequently in MAGE-A12-positive patients than that of the MAGE-negative controls. Furthermore, MAGA-A11 was reported to have a negative impact on treatment with cisplatin, 5-fluorouracil, paclitaxel and docetaxel (16). In the same study, MAGE-A5 was demonstrated to be associated with improved outcomes following paclitaxel therapy.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…As described by their group, N0 cervical lymph node status was found more frequently in MAGE-A12-positive patients than that of the MAGE-negative controls. Furthermore, MAGA-A11 was reported to have a negative impact on treatment with cisplatin, 5-fluorouracil, paclitaxel and docetaxel (16). In the same study, MAGE-A5 was demonstrated to be associated with improved outcomes following paclitaxel therapy.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, a previous study by our group identified a correlation between MAGE-A5 and -A8 expression and poorer responses to anti-epidermal growth factor receptor (EGFR) therapy in vitro (15). Of note, MAGE-A11 expression is also correlated with poorer responses to cisplatin, 5-fluorouracil, docetaxel and paclitaxel (16).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Cisplatin is a broad-spectrum anticarcinogen, which is also used in combination with hyperthermia (Issels, 2008). The tumor cell inhibition of high doses of cisplatin (80 and 120 μg/ml) at 24 h in vitro is above 80% (Hartmann et al, 2014;Su et al, 2012). Anucleated erythrocytes are little damaged by cisplatin in theory because the key molecular target of cisplatin is eukaryotic DNA (Issels, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…High expression levels of MAGE-A in HNSCC tumors are predictive for a poor overall survival (15,16). The correlation between the expression of a particular MAGE-A subgroup and the treatment efficiency of chemotherapeutic drugs was reported by our group earlier (17)(18)(19). Han et al showed that there is a significant correlation between high MAGE-A9 expression levels and a low overall survival in laryngeal squamous cell carcinoma patients (20).…”
Section: Introductionmentioning
confidence: 96%